Pengaruh Asimetri Informasi, Ukuran Perusahaan, Kepemilikan Institusionalterhadap Manajemen Laba Pada Perusahaan Manufaktur Di Bei Periode 2009-2012 - Cici Dessyaningrum Permata Herza; Errin Yani Wijaya; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study to examine the effect of information asymmetry on earnings management, to test the effect of firm size on earnings management and to test the effect of institutional ownership on earnings management. Population in this study are all publicly traded manufacturing company in Indonesia, which is listed on the Stock Exchange in 2009 until 2012. Total study population of 131 companies .. Companies that meet the criteria and were sampled as many as 35 companies. Analysis of research on the use of is using multiple linear regression equation with the help of software SPSS (Statistical Product and Service Solutions). Based on the first hypothesis suggests that there is a significant influence on the spread between earnings management in companies. The results of the t test for variables firm size, stating There is significant influence between the size of the Company's Earnings Management company. And the results of the t test of institutional ownership variables, stating there is no significant influence on the ratio between Institutional Ownership Profit Management company.Keywords: Information Asymmetry, Size, Institutional Ownership and Earnings Management